(untitled) (Huellas, 2015)
Cultural industries have gained a very important position in the preservation of cultureand national identity; so, fostering them becomes a key factor to be taken into account as part of the economic growth of countries. Besides, handicrafts’ activities as cultural industries play a key role within modern economies. The aim of this study is to analyze the importance of the production of handicrafts in the northern region of Jalisco after its being promoted as a regional tourism destination with cultural, economic and social purposes. This paper will present strategic alternatives that both the government and other institutions could implement in order to foster regional development through projects that involve cultural as well as handicrafts promotion in the northern region of Jalisco.